Changes in the Perception of the Teaching Profession in Polish Society - Kinal, Mariola (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
Economic, historical and social changes affect the changing perception of the teaching profession in Poland and around the world. With the increase in the availability of education, changes in the educational system, the way future teachers are trained and society’s attitude towards the work done by teachers is changing. The purpose of the article is to analyse the changes taking place in the perception of the teaching profession, including an analysis of historical changes and social conditions, as well as a comparison of social research on the prestige of the teaching profession, its image and factors affecting satisfaction with the work performed by teachers. The main research method was desk research.